EFEKTIVITAS PENAGIHAN TUNGGAKAN PAJAK PENGHASILAN DENGAN SURAT PAKSA SERTA KONTRIBUSINYA TERHADAP PENINGKATAN PENERIMAAN PAJAK PADA KPP PRATAMA SEKAYU - Farida Aryani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
A claim of tax arrears with compelling notice is a claim conducted by a state tax bailiff. This research has the purpose to know the effectiveness of tax arrears claim with compelling notice and the contribution of tax arrears claim with the compelling notice to the income tax acceptance of KPP Pratama Sekayu. This is a quantitative descriptive using effectiveness ratio calculating and contribution. This research uses secondary data in the form of the reports of tax arrears claim, income tax acceptance and the amount of tax payer from 2013 to 2017. The result of this research shows that tax arrears claim with compelling notice from 2013 to 2017 is not effective due to the fact that the ratio is less than 80%. That is only around 62,37% to 79,59%. Hence forth the contribution of tax arrears claim with compelling notice to the realization of tax acceptance at KPP Pratama Sekayu is considered very low due the fact that it’s contribution is less than 105, it is only around 0,38% - ).89%. The low contribution shows that the target of tax arrears with compelling notice is very low.